What is the importance of the psychopedagogical function of a sports trainer in improving club players' performance? - Gloria González Campos (FEADEF, 2010)
In this paper the more evolved tag games are defined and analyzed, that is, those characterized for throwing a soft object in order to hunt running away players. After reviewing the controversy about the adequacy of one of the clearest examples of this group of games, dodgeball, we argue the need to modify the rules to ensure their educational potential, and we consider a proposal of a new games category which could be addressed from an understanding approach. This family of games comes to complement the Almond's taxonomy (1986) and its curricular consideration could lead to possible implications on the transfer of tactical principles. Similarly, the article analyzes the structural and functional characteristics of this group of games, and defends the use of an, easy to create, homemade equipment, reducing the risk of causing damage to the opponent, and giving students the opportunity to invent their own games